SERUM YKL-40 LEVELS IN CHRONIC HEART FAILURE. - Maria Kazakova; Petar Nikolov; Kiril Simitchiev; Fedya Nikolov; Victoria Sarafian (Peytchinski Publishing, 2014)
Inflammatory processes are involved in the pathogenesis and development of chronic heart disease. The promising novel inflammatory biomarker YKL-40 is related to the degree of inflammation and pathological tissue remodeling. The aim of this study was to determine serum YKL-40 levels in patients with chronic heart failure and to evaluate the potential relationship with ultrasonography findings. Forty-three individuals were enrolled in the study - 24 patients (10 females and 14 males) with chronic heart failure, aged 70±11 (mean ± standard deviation) and 16 healthy people as age-matched controls (above 50 years). The serum YKL-40 levels were assessed by ELISA. Sonographic measurements such as two-dimensional, Power wave, Continuous Wave, Colour mode and M-Mode were performed using a diagnostic ultrasound system (PHILIPS Ultrasound, Washington, US) with a L11-3 probe of 3-11 MHz. The six minute walk test was used to assess functional capability of patients. Our study revealed significantly higher serum YKL-40 levels in patients compared to the control group (P=0.010). No relation was found between the glycoprotein and the results from the ultrasonographic and functional examination. We suppose that increased serum YKL-40 levels in patients with chronic heart failure might reflect the inflammatory route in the development of the disease.